Triangular Titanium Implants for Minimally Invasive Sacroiliac Joint Fusion: A Prospective Study - Duhon, Bradley S. (Global Spine J, 2015)
Study Design Prospective multicenter single-arm interventional clinical trial. Objective To determine the degree of improvement in sacroiliac (SI) joint pain, disability related to SI joint pain, and quality of life in patients with SI joint dysfunction who undergo minimally invasive SI joint fusion using triangular-shaped titanium implants. Methods Subjects (n = 172) underwent minimally invasive SI joint fusion between August 2012 and January 2014 and completed structured assessments preoperatively and at 1, 3, 6, and 12 months postoperatively, including a 100-mm SI joint and back pain visual analog scale (VAS), Oswestry Disability Index (ODI), Short Form-36 (SF-36), and EuroQOL-5D. Patient satisfaction with surgery was assessed at 6 and 12 months. Results Mean SI joint pain improved from 79.8 at baseline to 30.0 and 30.4 at 6 and 12 months, respectively (mean improvements of 49.9 and 49.1 points, p < 0.0001 each). Mean ODI improved from 55.2 at baseline to 32.5 and 31.4 at 6 and 12 months (improvements of 22.7 and 23.9 points, p < 0.0001 each). SF-36 physical component summary improved from 31.7 at baseline to 40.2 and 40.3 at 6 and 12 months (p < 0.0001). At 6 and 12 months, 93 and 87% of subjects, respectively, were somewhat or very satisfied and 92 and 91%, respectively, would have the procedure again. Conclusions Minimally invasive SI joint fusion resulted in improvement of pain, disability, and quality of life in patients with SI joint dysfunction due to degenerative sacroiliitis and SI joint disruption.